Study of the Chalcogenide Nonlinear Fiber Bragg Gratings for All-Optical Switching - Eliska Jurisova; Jarmila Mullerova (Communications - Scientific letters of the University of Zilina, 2012)
In this paper uniform and apodized nonlinear chalcogenide glass fiber Bragg gratings (FBG) as novel and promising devices for all-optical switching are investigated. The transmission response of these devices is discussed theoretically. The continuous wave in the investigated FBGs induces the nonlinear variation of the refractive index that causes changes in the FBG transmission characteristics. This effect can be modified depending on incident light power what is assumed to be due to the optical Kerr effect responsible for optical switching. The incident intensity thresholds of the bistable regimes were analyzed numerically to deduce possible switching properties of FBGs based on various chalcogenide glass samples. The influence of grating parameters on the optical bistability behaviour is researched. The nonlinear coupled mode theory was used for numerical investigation.